(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This research examines Public Service Ethics Based on Local Wisdom in the Cities of Makassar and Gowa, located in South Sulawesi Province, Indonesia. This study explains the important role of local wisdom in shaping the implementation of public service practices in the region. It observes the importance of raising awareness, fostering understanding, and encouraging active community involvement in the process of policy formulation and service implementation. These efforts are critical to effectively integrating local cultural values into the delivery of public services. Furthermore, this study examines the importance of regulatory frameworks that provide support, extensive training programs, and policy formulation that prioritizes local wisdom to improve the ethical standards of public administration. Preserving and preserving local wisdom is an important effort to strengthen cultural identity and heritage. The overall conclusion of this study is that the provision of culturally sensitive public services can result in more relevant and significant community engagement, while ensuring the preservation of valuable cultural heritage.